Variability patterns of the general circulation and sea water temperature in the North Sea. (June 2015) - Mathis, M.; Elizalde, A.; Mikolajewicz, U.; Pohlmann, T.
Highlights: We examine leading modes and sub modes of seasonal variability in the North Sea. We use a global ocean model with stretched grid configuration for a regional study. We identify circulation and temperature anomalies not caused by NAO variation. Sea water temperature shows different variability modes for winter and summer. Surface heat fluxes excite different variability modes than advective heat fluxes. Abstract: This study investigates patterns of spatio-temporal variability in the North Sea and their major driving mechanisms. Leading variability modes of the general circulation and sea water temperature are extracted from model results by means of Empirical Orthogonal Functions (EOF) analysis. The model results originate from an uncoupled simulation with the global ocean model MPIOM, forced with ERA40 reanalysis data at the air–sea interface. For this regional model study, MPIOM has been run with a stretched grid configuration enabling higher horizontal resolution in the Northwest European Shelf and North Atlantic ocean. The analysis is applied to interannual variabilities of winter and summer separately. The results indicate that on seasonal scales the leading variability mode of the general circulation affects the entire North Sea, accompanied by significant inflow anomalies through the Fair-Isle Passage. Correlations of the corresponding Principal Component (PC) with wind density functions reveal the circulation anomalies to coincide with westerly and south-westerly wind anomalies. The second mode describes circulation anomalies along the Norwegian Trench and English Channel, which correlate with north-westerly wind anomalies caused by variations in large-scale atmospheric pressure areas centered over the British Isles. For sea water temperature, distinct variability patterns are induced by variable surface heat fluxes, vertical mixing, and variable advective heat fluxes. The first mode of both the general circulation and water temperature in winter mainly represents the response to atmospheric variations in the North Atlantic Oscillation (NAO). However, the higher modes account for such variabilities that cannot be explained by the NAO. As a consequence of the integrated effects of the different variability modes on the circulation system and heat content, local correlations of the NAO with volume transports and water temperature are weakened in the regions of Atlantic inflow.